(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Artificial Intelligence (AI) is revolutionizing forensic medicine by enhancing the accuracy, efficiency, and scope of criminal investigations and victim identification. AI technologies, such as image and pattern recognition, DNA analysis, and predictive analytics, offer unique opportunities to improve forensic practices. However, the integration of AI into forensic medicine presents significant challenges, including technological implementation, data security, infrastructure needs, and training of professionals. Furthermore, ethical implications surrounding privacy, accountability, bias, consent, and human rights are central to the responsible use of AI in forensic contexts. The collection of sensitive personal data and the potential for AI to influence critical legal decisions raises concerns about transparency, fairness, and the protection of individual rights. To ensure the responsible application of AI in forensic medicine, it is essential to develop comprehensive guidelines, regulations, and ethical frameworks. As AI technology evolves, balancing innovation with ethical considerations will be crucial. Future progress in AI in forensic medicine will require ongoing collaboration between forensic scientists, AI researchers, legal professionals, and policymakers. By addressing these challenges and ethical dilemmas, the integration of AI can significantly enhance justice, public safety, and victim closure, while maintaining the integrity of the justice system. Ultimately, the successful integration of AI into forensic practices depends on caution, foresight, and a commitment to ethical principles to safeguard both technological advancements and fundamental human rights.